My Life - Clinton, Bill, 1946- (New York, : Vintage Books, 2004)
President Bill Clinton's My Life is the strikingly candid portrait of a global leader who decided early in life to devote his intellectual and political gifts, and his extraordinary capacity for hard work, to serving the public. It shows us the progress of a remarkable American, who, through his own enormous energies and efforts, made the unlikely journey from Hope, Arkansas, to the White House--a journey fueled by an impassioned interest in the political process which manifested itself at every stage of his life: in college, working as an intern for Senator William Fulbright; at Oxford, becoming part of the Vietnam War protest movement; at Yale Law School, campaigning on the grassroots level for Democratic candidates; back in Arkansas, running for Congress, attorney general, and governor. We see his career shaped by his resolute determination to improve the life of his fellow citizens, an unfaltering commitment to civil rights, and an exceptional